2022
DOI: 10.3390/cells11131996
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic CREB Regulates the Expression of Pomc-Processing Enzyme Pcsk2

Abstract: Background: The hypothalamic proopiomelanocortin (Pomc) neurons act as first-order sensors of systemic energy stores, providing signals that regulate caloric intake and energy expenditure. In experimental obesity, dietary saturated fatty acids affect Pomc endopeptidases (PCs), resulting in the abnormal production of the neurotransmitters α-melanocyte-stimulating hormone (α-MSH) and β-endorphin, thus impacting energy balance. The cAMP response element-binding protein (CREB) is one of the transcription factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The transcriptional level of POMC is regulated by the transcription factor CREB, which is phosphorylated at serine-133 and translocates to the nucleus to bind to target gene promoters. 20,21 We detected lower levels of p-CREB (serine-133) following BMPSB4 treatment, and the RNA sequencing results also suggested changes in the cAMP signaling pathway. These results suggest that POMC inhibition by BMPSB4 may be achieved by inhibiting the cAMP−PKA− CREB signaling pathway.…”
Section: Acs Pharmacologymentioning
confidence: 78%
See 1 more Smart Citation
“…The transcriptional level of POMC is regulated by the transcription factor CREB, which is phosphorylated at serine-133 and translocates to the nucleus to bind to target gene promoters. 20,21 We detected lower levels of p-CREB (serine-133) following BMPSB4 treatment, and the RNA sequencing results also suggested changes in the cAMP signaling pathway. These results suggest that POMC inhibition by BMPSB4 may be achieved by inhibiting the cAMP−PKA− CREB signaling pathway.…”
Section: Acs Pharmacologymentioning
confidence: 78%
“…Previous studies have emphasized the significance of CREB phosphorylation in ACTH production. 20,21 Western blotting indicated that BMPSB4 reduced p-CREB levels in a concentration-dependent manner (Figure 3H). POMC encodes a preproprotein that produces ACTH after tissue-specific posttranslational processing.…”
Section: Acs Pharmacology and Translational Sciencementioning
confidence: 98%
“…Our results are in agreement with data demonstrating the implication of the CREB/CRE transcriptional pathway in circadian clock timing in the suprachiasmatic nucleus, the locus of the master mammalian clock [ 51 ]. Furthermore, it was shown that the inhibition of hypothalamic CREB using a short-hairpin RNA lentiviral vector resulted in increased body-mass gain and reduced energy expenditure [ 52 ]. These findings are in agreement with the results of the present work, indicating a body weight rise in CBA mice exposed to a short photoperiod.…”
Section: Discussionmentioning
confidence: 99%
“…Beta endorfin endorphin is an endogenous opioid neuropeptide and peptide hormone that is produced in certain neurons within the central nervous system and peripheral nervous system. It is one of three endorphins that are produced in humans, the others of which include α-endorphin and γ-endorphin [8,9,10].…”
Section: About Mifepristone About Mifepristonementioning
confidence: 99%